Effects of silane-modified fillers on properties of dental composite resin - Aydinoglu, Aysu; Yoruc, Afife Binnaz Hazar (ELSEVIER, 2017)
The effect of silanization on the mechanical, chemical, and physical properties of dental composites was investigated. Silica fillers were obtained from colloidal silica solution, Ludox (R) HS40 and they were silanized by using 3methacryloxypropyl trimethoxysilane (MPTMS) in an acidic media. Mineralogical and chemical structures of unsilanized and silanized fillers were determined by using XRD and FTIR analyses. The modification of unsilanized/silanized fillers were investigated by performing XPS and TGA analyses. The morphological evaluations, surface area, and particle size measurements were performed by using SEM, BET, and ZetaSizer, respectively. Eventually, pure and amorphous silica fillers were obtained. Furthermore, the weight percentage of the silane in silica/silane structure was compatible with theoretical values. SEM images, surface area, and particle size measurements showed that agglomeration tendencies of silanized fillers were lower compared to silanized fillers because of the MPTMS addition. Experimental composites (5/10/10/5BisGMA/HEMA/UDMA/TEGDMA resin reinforced with 70 wt% silanized/unsilanized SiO2) were fabricated into 4 mm diameter x 6 mm thick discs for compressive strength (CS), angular flexural strength (AFS), curing depth (CD), and polymerization shrinkage (PS) on a 25 x 2 x 2mm rectangular Teflon mold for flexural strength (FS) and modulus of elasticity (E) tests. The curing depth (CD) and degree of polymerization percentage (DP) of composites were determined. Consequently, results showed that mechanical properties and DP of composite resins can be greatly influenced by silanization as a result of the organic matrix inorganic filler interface bonding formed by silane structures. Despite of these findings, silanization of the SiO2 was not effected DC and PS values. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Dental composite resin; Bis-GMA resin; UDMA resin; HEMA; Inorganic fillers; Silica; Bonding agents; Silanes; 3-MPTMS; MECHANICAL-PROPERTIES; SURFACE MODIFICATION; NANOPARTICLES; SHRINKAGE; NANOCOMPOSITES; ANTIBACTERIAL; MICROLEAKAGE; DENTISTRY; SORPTION; SIO2; Materials Science